2005
DOI: 10.1007/s00125-004-1667-1
|View full text |Cite
|
Sign up to set email alerts
|

Fibrinogen and AER are major independent predictors of 11-year cardiovascular mortality in type 2 diabetes: the Casale Monferrato Study

Abstract: Aims/hypothesis: Fibrinogen and elevated AER increase cardiovascular mortality, but few data are available in the type 2 diabetic population. We have conducted an 11-year follow-up study of the Casale Monferrato cohort to assess: (1) the long-term predictive role of AER independently of conventional risk factors; (2) the shape of its relationship with cardiovascular mortality; and (3) whether fibrinogen has a predictive effect independent of the increased cardiovascular risk associated with nephropathy. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
49
0
1

Year Published

2005
2005
2011
2011

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 45 publications
(54 citation statements)
references
References 39 publications
4
49
0
1
Order By: Relevance
“…It has been previously reported that type 2 diabetic patients are characterised by elevated fibrinogen synthesis and plasma levels [5,6]. Our data confirm this observation and demonstrate that LPD is able to reduce ASR of fibrinogen, although it did not significantly reduce fibrinogen FSR.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…It has been previously reported that type 2 diabetic patients are characterised by elevated fibrinogen synthesis and plasma levels [5,6]. Our data confirm this observation and demonstrate that LPD is able to reduce ASR of fibrinogen, although it did not significantly reduce fibrinogen FSR.…”
Section: Discussionsupporting
confidence: 90%
“…Once patients with microalbuminuria progress to macroalbuminuria (overt nephropathy), they are likely to progress to end-stage renal disease [3]. Diabetic nephropathy is often associated with low-grade inflammation [4], hyperfibrinogenaemia [5], dyslipidaemia and high incidence of cardiovascular morbidity and mortality [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Models included conventional risk factors (age, sex, smoking, hypertension, CHD), novel risk factors (AER, fibrinogen) and cumulative individual average HbA 1c during follow-up (time-dependent variable). The HRs were also adjusted for referring physician, as previous analyses of the Casale Monferrato cohort identified this as a significant predictor of mortality [24]. Given the time scale, all the models were also adjusted for known duration of diabetes.…”
Section: Methodsmentioning
confidence: 99%
“…This cohort has been followed prospectively to determine 11-year mortality from all causes and from cardiovascular disease [22][23][24]. As the association of the ApoB:ApoA-I ratio has not been studied in a population-based cohort of people with diabetes, the aims of the analysis reported here were: (1) to investigate the association between plasma lipids, lipoprotein lipids and apolipoprotein with mortality from cardiovascular disease; and (2) to assess whether age modifies any of these relationships.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Hence, identification of markers of increased risk for development of cardiovascular disease (CVD), that add to established risk parameters for CVD such as smoking, 4 cholesterol level, 5 albuminuria 6,7 and creatinine level, 8 is important.…”
Section: Introductionmentioning
confidence: 99%